Frequency and course of COVID-19 in patients with rheumatic diseases (according to the data of V.A. Nasonova Research Institute of Rheumatology) - A. N. Kulikov; N. V. Muravyeva; B. S. Belov (Научно-практическая ревматология)
The aim of the study was to assess frequency and severity of COVID-19 in patients with rheumatic diseases (RD) who were on inpatient treatment at the V.A. Nasonova Research Institute of Rheumatology. Patients and methods. The study included information on the presence or absence of COVID-19 in the medical history of 6911 patients with immunoinflammatory RD (IIRD) and 362 patients with osteoarthritis (OA) who were on inpatient treatment at the V.A. Nasonova Research Institute of Rheumatology from September 21, 2021 to April 28, 2023. Results. The incidence of COVID-19 in the analyzed IIRD was significantly higher compared to OA (p<0.001). All IIRD included in the analysis are characterized by an increased risk of COVID-19 incidence when compared with OA by 2.7–6.3 times. Patients with rheumatoid arthritis, ankylosing spondylitis, psoriatic arthritis, microcrystalline arthritis, Sjögren’s disease, systemic sclerosis, systemic lupus erythematosus, and ANCA-associated vasculitis were significantly more likely (p<0.02) to receive COVID-19 therapy compared with the control group. Patients with these diseases are characterized by an increased risk of treatment for COVID-19 by 1.9–3.7 times compared with OA. Also, patients with inflammatory joint diseases (IJD), connective tissue diseases (CTDs) and systemic vasculitis (SV) were hospitalized with COVID-19 more often than patients with OA (p=0.01, p=0.007 and p=0.024, respectively). Patients with IJD, CTDs and SV are characterized by an increased risk of hospitalization with COVID-19 by 4.3– 4.7 times compared with OA. In addition, elderly patients with IIRD are characterized by an increasing risk of treatment, hospitalization and use of biologics or targeted synthetic disease-modifying drugs for COVID-19. Conclusion. According to the results obtained, the problem of COVID-19 is significant for patients with RD, which dictates need for further research on vaccination against SARS-CoV-2 among this cohort of patients.